2018
DOI: 10.1038/s41598-018-23176-x
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionarily conserved genes: Tex37, Ccdc73, Prss55 and Nxt2 are dispensable for fertility in mice

Abstract: There are more than 2300 genes that are predominantly expressed in mouse testes. The role of hundreds of these genes has been studied in mouse spermatogenesis but still there are many genes whose function is unknown. Gene knockout (KO) strategy in mice is widely used for in vivo study of gene function. The present study was designed to explore the function of the four genes: Tex37, Ccdc73, Prss55 and Nxt2, which were evolutionarily conserved in eutherians. We found that these genes had a testis-enriched expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
1
31
2
Order By: Relevance
“…Despite how these molecules affect the presence of mature ADAM3 on the sperm surface, an essential role for mature ADAM3 and other ADAMs that are modulated by serine proteases, such as PRSS37 and PRSS55, during the process of fertilization should not be neglected. Additionally, another group also reported that PRSS55 is dispensable for male fertility in mice (Khan et al, ). This discrepancy may be due to the different genetic backgrounds of the two groups of mice (Khan et al, ; Shang et al, ).…”
Section: Testis‐specific Serine Proteases (Prss37 and Prss55)mentioning
confidence: 98%
See 1 more Smart Citation
“…Despite how these molecules affect the presence of mature ADAM3 on the sperm surface, an essential role for mature ADAM3 and other ADAMs that are modulated by serine proteases, such as PRSS37 and PRSS55, during the process of fertilization should not be neglected. Additionally, another group also reported that PRSS55 is dispensable for male fertility in mice (Khan et al, ). This discrepancy may be due to the different genetic backgrounds of the two groups of mice (Khan et al, ; Shang et al, ).…”
Section: Testis‐specific Serine Proteases (Prss37 and Prss55)mentioning
confidence: 98%
“…Therefore, PRSS37 and PRSS55, as serine proteases, were more likely to modulate the posttranslational modifications of ADAM3 reported that PRSS55 is dispensable for male fertility in mice (Khan et al, 2018). This discrepancy may be due to the different genetic backgrounds of the two groups of mice (Khan et al, 2018;Shang et al, 2018). Mice with different genetic backgrounds may have slightly different functions for a particular gene.…”
Section: Testis-specific Serine Proteases (Prss3and Prss55)mentioning
confidence: 99%
“…These are TEX37 (Testis Expressed 37), SYCP2L (Synaptonemal Complex Protein 2 Like) and IL15 (Interleukin 15); they are not associated with GC bias nor located in GC-rich regions. TEX37 is predominantly expressed in the testis [38] while SYCP2L is mainly expressed in the ovary [39]. In addition, gene association studies report a correlation between SYCP2L variants and lipid metabolism, although the mechanism remains unknown [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Among testis‐specific genes or genes predominantly expressed in testis, both in mice and in humans, at least 54 showed no effect on male fertilizing ability upon gene disruption . Recently, another four genes were added to this list . All genes may have some role in the body, but their functions range from important to unimportant.…”
Section: A Specific Expression Pattern Does Not Necessarily Mean a Spmentioning
confidence: 99%